Globalization and poverty: Evidence for lower-middle income country - Philip Ifeakachukwu Nwosa; Temitope Adebisi Adeoye (Economic Review: Journal of Economics and Business, 2021)
The study examined the impact of globalization on poverty rate with evidence from middle-income country. It focused on Nigeria for the period spanning 1981 to 2018. The study employed the ARDL estimation technique, and the results showed that globalization had negative and significant impact on poverty rate in Nigeria. Therefore, the conclusion was made that globalization had contributed significantly in reducing poverty rate in Nigeria. The study recommended the need for the government to maintain strong economic and political global ties with the rest of the world. This would encourage more foreign investors and business opportunities in the country which would aid reduction of poverty rate in Nigeria. More so, there is the need to ensure that the dividend of economic growth from globalization is properly shared among the poor, as this would reduce the number of the poor people below the poverty line.
Keywords: F15; I32; 330; globalization; poverty; ARDL; Nigeria